1984
DOI: 10.1152/ajprenal.1984.246.5.f600
|View full text |Cite
|
Sign up to set email alerts
|

Effects of luminal fluid anions on calcium transport by proximal tubule

Abstract: To determine whether the anion composition of tubule fluid affects calcium absorption by the renal proximal tubule, in vivo microperfusion techniques were employed in anesthetized rats. Experiments were designed so that total calcium and sodium concentrations were kept constant in fluids entering the tubule. A control solution, in which the main anion was chloride, was modified either by addition of ethyleneglycol-bis(beta-aminoethylether)-N,N'-tetra-acetic acid or by replacing most of the chloride with nitrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…Micropuncture studies have found that about 60% of filtered Ca2+ is reabsorbed in segment 1 and 2 of the proximal convoluted tubule, and 10% in the proximal straight tubule [13 ,17, 31]. It has been proposed that nearly all Ca2+ absorption in these tubules is passive and occurs via the paracellular route [1,5,21]. The present findings in segment 2 and 3 of the proximal tubules support the paracellular pathway of Ca2+ absorption.…”
Section: Localization Of Ca2+in Nephronssupporting
confidence: 74%
“…Micropuncture studies have found that about 60% of filtered Ca2+ is reabsorbed in segment 1 and 2 of the proximal convoluted tubule, and 10% in the proximal straight tubule [13 ,17, 31]. It has been proposed that nearly all Ca2+ absorption in these tubules is passive and occurs via the paracellular route [1,5,21]. The present findings in segment 2 and 3 of the proximal tubules support the paracellular pathway of Ca2+ absorption.…”
Section: Localization Of Ca2+in Nephronssupporting
confidence: 74%
“…(----in), BLMV The demonstration of active Ca2`reabsorption in the proximal nephron (7) indicates an important role of transcellular calcium movements in the reabsorptive fluxes of this segment. This implies both an apical influx and basolateral efflux step for calcium in the proximal cell.…”
Section: Resultsmentioning
confidence: 99%
“…These findings have been criticized on technical grounds (6). However, recent findings of Bomsztyk and Wright (7,8) confirm the presence of net Ca2+ absorption in the absence of transepithelial electrochemical driving forces which indicate active Ca2+ transport. In these studies, there was also clear dissociation between Na+ and Ca2+ transport rates in certain experimental settings.…”
mentioning
confidence: 90%
“…Male Sprague-Dawley rats (Bantin & Kingman, Freemont, CA) weighing 250-300 g were anesthetized by intraperitoneal injection of 5-sec-butyl-2-ethyl thiobarbituric acid (Inactin, Byk-Gulden, Konstanz, Federal Republic of Germany) (100 mg/kg body weight) and were prepared for in vivo micropuncture and microperfusion as previously described (6,7). A continuous intravenous infusion ofsolution containing 140 mM NaCl and 4.0 mM KCI at a rate of0.1 ml/min per kg body weight was administered and arterial blood pressure was monitored throughout the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…With the recent introduction of Ca2" ion selective microelectrodes direct in situ measurements are now possible (6).…”
Section: Introductionmentioning
confidence: 99%